Ethnic Group Map Learning Media Based on the Global Diversity of Bhinneka Tunggal Ika in Social Studies for Grade V Elementary School Students - Ni Nyoman Ayu Citra Dewi; Anak Agung Gede Agung; I Gede Astawan (Universitas Pendidikan Ganesha, 2025)
Social studies learning in primary schools still faces obstacles in delivering material on ethnic diversity, which tends to be abstract. The lack of interactive learning media results in low student comprehension. This study aims to develop, test the validity, and analyse the effectiveness of an interactive learning medium based on the global diversity of Bhineka Tunggal Ika. The research method used is Research and Development (R&D) with the ADDIE model. The research subjects consisted of 3 experts (content expert, design expert, and media expert) and 30 fifth-grade elementary school students. Data collection was conducted through questionnaires and tests. Questionnaires were used to assess the validity of the product by experts and student responses, while tests were used to measure the effectiveness of the media through pre-test and post-test designs. The validation results showed scores of 95.45% (content expert), 91.66% (design expert), and 95% (media expert) in the ‘very good’ category. The effectiveness test using a t-test showed tcalculated = -4.35 > ttable = 1.655, indicating a significant improvement in students' understanding. In conclusion, the Bhinneka Tunggal Ika global diversity-based ethnic group map learning media proved to be feasible and effective in improving students' understanding of social studies in primary schools. The implication of this study is that the use of visual-based media can strengthen the quality of learning and serve as a reference in the development of digital media in primary education.